2022
DOI: 10.1055/s-0042-1749598
|View full text |Cite
|
Sign up to set email alerts
|

Dashboard Design to Identify and Balance Competing Risk of Multiple Hospital-Acquired Conditions

Abstract: Background Hospital-acquired conditions (HACs) are common, costly, and national patient safety priority. Catheter-associated urinary tract infections (CAUTIs), hospital-acquired pressure injury (HAPI), and falls are common HACs. Clinicians assess each HAC risk independent of other conditions. Prevention strategies often focus on the reduction of a single HAC rather than considering how actions to prevent one condition could have unintended consequences for another HAC. Objectives The objective of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…39,40 This approach contrasts with information being fragmented among multiple pages in the EMR. 39,40 Additionally, such tools can be particularly powerful when representing dynamic time frame data. For instance, an e-antibiogram, generated and regularly updated from both laboratory and pharmacy data, presents a viable alternative to the static, manually compiled antibiogram typically produced annually.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…39,40 This approach contrasts with information being fragmented among multiple pages in the EMR. 39,40 Additionally, such tools can be particularly powerful when representing dynamic time frame data. For instance, an e-antibiogram, generated and regularly updated from both laboratory and pharmacy data, presents a viable alternative to the static, manually compiled antibiogram typically produced annually.…”
Section: Discussionmentioning
confidence: 99%
“…38 Makic et al and Zaydfudim et al suggested that dashboards have the potential to help clinicians address overlapping risks and potential patient harm in the unit by managing multiple values for preidentified health care-associated infection risk. 39 40 This approach contrasts with information being fragmented among multiple pages in the EMR. 39 40 Additionally, such tools can be particularly powerful when representing dynamic time frame data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to participants, workflow fragmentation originated from physical disruptions by colleagues, inadequate computer peripherals (eg, single computer screen), and the EHR software (eg, interruptive alerts, display, and task fragmentation 47 ). Described elsewhere in the literature as a cause of EHR cognitive burden, 63 display fragmentation 47 (ie, the need to click through several screens and views due to disjoint information), and task fragmentation 47 (ie, “undesirable” separation of task components) in the EHR was reported as a design flaw and key driver of task switching among participants. Moreover, clinicians perceived that reimbursement, regulatory, and reporting requirements not only fragmented clinician documentation workflows but also resulted in poor documentation quality as it splintered the patient’s narrative.…”
Section: Discussionmentioning
confidence: 99%
“…These studies report on dashboard performance as measured by end user uptake, usability, or associated improvement in health outcomes, with some detail provided on which factors in their development process were believed to contribute to the dashboard's successes. 7 8 9 10 11 12 There is growing consensus that involving clinicians in the development process of audit and feedback clinical dashboards is important to ensure that user needs are adequately met prior to releasing the dashboard for routine use, subsequently improving uptake and adoption. 13 14 This principle has long been understood in the field of human-centered design, which seeks to systematically integrate end-user feedback throughout the development process.…”
Section: Background and Significancementioning
confidence: 99%